Analisis Metode Pembayaran Online SevimaPay Menggunakan Technology Acceptance Model (TAM) Pada Perguruan Tinggi Swasta Bukittinggi - Dini Fitriyanthi (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
This study aims to analyze the factors that influence interest in using the SevimaPay online payment method using the Technology Acceptance Model (TAM) analysis. The Technology Acceptance Model (TAM) method is used to measure technology acceptance using manufacturing modules with variables of perceived usefulness (PU), perceived ease of use (PEOU), and perceived risk (PR) which influence behavioral intention of use (BIU) and perceived ease of use. use (PEOU) affects perceived usefulness (PU). Data collection was carried out by giving questionnaires to respondents as users of the SevimaPay online payment method at one of the Private University in Bukittinggi. Data measurement using SmartPLS. The results of this study indicate that perceived usefulness, perceived ease of use and perceived risk have a significant effect on behavioral intention. Meanwhile, perceived ease of use also has a significant effect on perceived usefulness.